Esophageal Foreign Body in a Neonate: An Unusual Age of Presentation - Singh, H; Dhingra, B; Yadav, D; Aggarwal, V (Journal of Nepal Paediatric Society, 2012)
Ingestion of foreign bodies in neonates is very rare and can be life threatening. We describe a 20 days old neonate presented with vomiting, drooling of saliva and poor feeding tolerance. Chest radiograph showed a metallic foreign body in superior mediastinum. Foreign body was removed by rigid oesophagoscopy. The case describes the unusual age of presentation of foreign body and options available to remove these foreign bodies in neonates. Key words: Esophagus; Foreign body; Neonate DOI: http://dx.doi.org/10.3126/jnps.v32i1.5306 J. Nepal Paediatr. Soc. Vol.32(1) 2012 79-80